Designing Physics Learning Based on Local Potential During New Normal Era - Indah Slamet Budiarti; Winarti Winarti; Viyanti Viyanti (Yayasan Keluarga Guru Mandiri, 2022)
This research explored and looked forward to the competencies and objectives of the feasibility of learning designs needed for the post-quarantine era of the COVID-19 pandemic in Indonesia, especially in Papua. The research method used in our study is qualitative which focuses on structural analysis to answer problems in the research found through preliminary studies. Our research sites are located in several educational institutions in Papua. The study population was all students at the elementary, junior high, high school and university levels in Papua, Indonesia. We used a sampling method in the form of a purposive sampling technique.Â The samples were three academic institutions; SMP N 5 Jayapura, SMA Pembangunan V Yappis, and Universitas Cenderawasih. Research instruments for collecting data were in the form of interview sheets, observation sheets, and questionnaires related to physics learning in the new normal era. The results of the study found that the physics learning design based on local potential in the new normal era can be an alternative for teaching physics concepts contextually. Students can observe the surrounding environment related to local customary culture which is indigenous science and educators represent the report in the form of a connection between the concept of science and local culture.